State ownership and Brazilian multinational enterprises: degree of internationalization and financial performance - Carrera Junior, José Marcos (2018)
State-owned enterprises (SOEs) are a mechanism adopted by emerging countries to fulfill the need for investment in specific areas. Under import substitution industrialization (ISI) policy marked by state intervention in the economy, SOEs and national private companies became protected from foreign competition and enjoyed great market power. However, economic shocks during the 1970s and 1980s, along with the growing inefficiency of these enterprises due to agency problems, led to losses. During the 1990s, Latin-American countries opened their economy and undertook privatization programs. However, since strong national companies may be useful for the State because they control strategic resources, and in order to maintain national sovereignty by preventing the acquisition of SOEs by foreign investors, the Brazilian State kept a minority equity stake in these companies. In addition, the Brazilian State also invested in some companies to make them globally competitive ('national champions'), while also holding minority equity stakes to avoid their acquisition by foreigners. We argue that the government has not abandoned its previous policy of intervention in the economy, instead, it has adapted it to new circumstances. We evaluate the influence of state ownership on the companies’ degree of internationalization and performance. SOEs may perform worse than privately controlled firms because of agency problems, while government as a minority shareholder can assist firms by providing financial and political resources. Analyzing a panel of non-financial listed companies in Brazil between 2002 and 2016, we found that the higher the state ownership by means of pension funds and BNDES, the higher the degree of internationalization measured by the foreign sales to total sales ratio. The degree of internationalization was even higher when the government was the minority shareholder of family-controlled companies. Analyzing the impact of state ownership on firm-level financial performance, we found that firms in which the government was one of the shareholders did not underperform in comparison to privately controlled firms before the Brazilian crisis of 2014- 2016 crisis. However, during the crisis, when government support decreased, we verified that the relation between majority state ownership and financial performance measured by the return on assets (ROA) and Tobin’s Q was negative. Although negative, there was no statistically significant effect of minority state ownership. Our study suggests the need for governmentinvested enterprises to develop skills to perform well when they cannot rely on government assistance. Furthermore, the degree of internationalization did not soften the effects of the crisis on the firm-level financial performance, which may indicate that the domestic institutional environment has a strong influence on the performance of Brazilian companies.